2005
DOI: 10.1016/j.orthres.2005.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Cellular basis for age-related changes in fracture repair

Abstract: The goal of this work was to define cellular and molecular changes that occur during fracture healing as animals age. We compared the molecular, cellular, and histological progression of skeletal repair in juvenile (4 weeks old), middle-aged (6 months old), and elderly (18 months old) mice at 3, 5, 7, 10, 14, 21, 28, and 35 days post-fracture, using a non-stabilized tibia fracture model. Our histological and molecular analyses demonstrated that there was a sharp decline in fracture healing potential between ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(147 citation statements)
references
References 6 publications
8
135
1
3
Order By: Relevance
“…Geriatric and osteoporotic patients may have a different biological potential for wound healing than nongeriatric, nonosteoporotic patients based on preclinical studies suggesting a reduction in lineage progression and proliferative activity of osteoblast progenitor cells and gene expression, a decrease in osteoblast function, diminished osteoblast response to signaling cues, and an imbalance between the coupling of bone formation and resorption. 2,[4][5][6][7][8]11,22,29,30 Therefore, the biological properties of rhPDGF-BB may be an important therapeutic consideration for geriatric and osteoporotic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geriatric and osteoporotic patients may have a different biological potential for wound healing than nongeriatric, nonosteoporotic patients based on preclinical studies suggesting a reduction in lineage progression and proliferative activity of osteoblast progenitor cells and gene expression, a decrease in osteoblast function, diminished osteoblast response to signaling cues, and an imbalance between the coupling of bone formation and resorption. 2,[4][5][6][7][8]11,22,29,30 Therefore, the biological properties of rhPDGF-BB may be an important therapeutic consideration for geriatric and osteoporotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In the osteoporotic and elderly, there is a reduction in lineage progression [4][5][6] and proliferative activity of osteoblast progenitor cells and gene expression, 7 a decrease in osteoblast function, 8 diminished osteoblast response to signaling cues, and an imbalance between the coupling of bone formation and resorption (reviewed 2 ). Consequently, bone healing in elderly and osteoporotic individuals may be delayed and new bone quality may be poor.…”
Section: Introductionmentioning
confidence: 99%
“…10 Ischemic and control animals with nonstabilized fractures were sacrificed at 3 and 5 days postfracture (n ¼ 5/time for both ischemic and control groups). Fracture tissue was fixed in 4% paraformaldehyde (PFA), decalcified in 19% EDTA, and frozen sections of 20 mm were prepared.…”
Section: Visualization Of Blood Vessels In the Hind Limbsmentioning
confidence: 99%
“…Animals with non-stabilized fractures (n ¼ 5/time for both ischemic and control groups) were sacrificed at multiple time points post-injury (3,5,7,10,14,21, and 28 days) to assess the effect with ischemia on different aspects of fracture healing. Animals with stabilized fractures (n ¼ 5/ time for both ischemic and control groups) were sacrificed at 10 and 14 days post-fracture when the cartilage should be most abundant if there is an affect on chondrogenesis.…”
Section: Histological and Molecular Analysesmentioning
confidence: 99%
“…We focused our assessments on days 10 and 28 because the peak of osteogenesis occurs between 10 to 14 days after fracture and because cartilage replacement with bone in the callus to bridge the fracture gap is usually completed by 28 days. (8,23) mCT imaging demonstrated that the bone fracture gap was bridged by bony tissue by day 28 ( Fig. 2A, Supporting Fig.…”
Section: Resultsmentioning
confidence: 96%